Identification of the distiller based on neuro-fuzzy network - Смітюх, Ярослав Володимирович; Кишенько, Василь Дмитрович (Eastern-European Journal of Enterprise Technologies, 2012)
Considered questions, authentications of such difficult object as bragorektifikaciyna setting related to basic theoretical and practical principles. The approaches considered in the article can be used for development of simulation models heat-masobminnikh of processes